Kebijakan Bank Indonesia Dalam Mendorong Perkembangan Teknologi Melalui Sistem Pembayaran Non Tunai - Aldi Lutfi Nuraha; Dika Diaulhaq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Digital transformation has brought significant changes to the payment system in Indonesia, shifting from cash-based transactions to non-cash payment methods. This study aims to examine the role and policies of Bank Indonesia in supporting the use of technology through digital payment systems. The method used is descriptive qualitative, relying on secondary data from various credible sources. The findings indicate that Bank Indonesia has taken strategic steps through policies such as the implementation of QRIS, the development of BI-FAST, the National Standard for Open API Payments (SNAP), and the Digital Rupiah initiative. These policies have successfully strengthened the national payment system by providing services that are fast, secure, accessible, and support the expansion of financial inclusion. However, challenges remain, particularly in terms of user data protection and the need for regulations that are responsive to technological developments. The results highlight the importance of adaptive policies and cross-sector collaboration in creating an efficient and sustainable digital payment system.